2014 Guideline for Management of Wounds in Patients With Lower-Extremity Arterial Disease (LEAD): An Executive Summary. Issue 1 (January 2016) - Bonham, Phyllis A.; Flemister, Bonny G.; Droste, Linda R.; Johnson, Jan J.; Kelechi, Teresa; Ratliff, Catherine R.; Varnado, Myra F.
Abstract : The purpose of this article is to provide a summary of the recommendations from the 2014 Guideline for Management of Wounds in Patients With Lower-Extremity Arterial Disease (LEAD), published by the Wound, Ostomy and Continence Nurses Society (WOCN). This article provides an overview of the process used to update and develop the guideline, and specific recommendations from the guideline for assessment, referral for further evaluation, interventions (ie, debridement, dressings, infection, antibiotics, nutrition, pain management, compression issues, medications, surgical options, and adjunctive therapies), and patient education and risk-reduction strategies. The LEAD guideline is a resource for physicians, nurses, therapists, and other healthcare professionals who work with adults who have/or are at risk for wounds due to LEAD. The full text of the published guideline, which includes the available evidence supporting the recommendations and a complete reference list, is available from the WOCN Society, 1120 Rt. 73, Suite 200, Mount Laurel, NJ, 08054; Web site:www.wocn.org . Refer to the Supplemental Digital Content (Supplement Digital Content 1, http://links.lww.com/JWOCN/A31 ) associated with this article for the complete reference list for the guideline. The guideline has been accepted for publication by the National Guideline Clearinghouse (www.guideline.gov/ ). Abstract : Supplemental Digital Content is Available in the Text.